Condutas terapêuticas para caninos inclusos - Gaetti-Jardim, Ellen Cristina [UNESP]; Faria, Karina Morais [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Gaetti-Jardim Júnior, Elerson [UNESP]; Saad Neto, Michel [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Ponzoni, Daniela [UNESP] (My University, 2012)
Normally, the last teeth to erupt are the ones which remain impacted or semi-impacted, and that is the case of the canines. This study aimed to report a few options of treatment, aiming at esthetic and functional maintenance of the affected area before a impacted canine, discussing its indications, contraindications, advantages and disadvantages. This study also aims to emphasize the accessibility the patient would have in case his/her option were one of the approached ways of treatment. In order to identify the studies included or analyzed in this review, a detailed search strategy was performed for the database used: Pubmed, Bireme, Scielo, Cochrane, and Dentistry Oral Science up to 2011. We used non-erupted teeth, canine, and therapeutics as descriptors. The criteria of inclusion were clinical and review articles that approached the theme. Through this review, it was found that the surgeon dentist’s lack of technical and scientific knowledge and the financial impossibility of most population are some hindrances for the establishment of the right planning for the impacted canine.

Normalmente, os últimos dentes a erupcionar são os que permanecem inclusos ou semi-inclusos, como é o caso dos caninos. O estudo teve como objetivo relatar algumas opções de tratamento a fim da manutenção estética e funcional da área atuada diante de um canino incluso, discutindo as suas indicações, contra-indicações, vantagens e desvantagens. Este trabalho também busca enfatizar a acessibilidade que o paciente teria caso a sua opção ideal fosse uma das formas de tratamento abordadas. Para a identificação dos estudos incluídos ou considerados nesta revisão, foi realizada uma estratégia de busca detalhada para os bancos de dados pesquisados: Pubmed, Bireme, Scielo, Cochrane e Dentistry Oral Science até o ano de 2011. Foram utilizados como descritores: dente não-erupcionado, canino e terapêutica. Os critérios de inclusão foram: artigos clínicos e de revisão que abordavam o tema. Foi constatado mediante esta revisão que a falta do conhecimento técnico-científico por parte do cirurgião-dentista e a impossibilidade financeira da maioria da população são alguns dos empecilhos para o estabelecimento do correto planejamento para o canino incluso.
Therapeutic behavior for impacted canines
Keywords: Tooth; Unerupted; Cuspid; Therapeutics; Dente não-Erupcionado; Dente Canino; Terapêutica